Green Chemistry Practicum to Enhance Students’ Learning Outcomes on Reaction Rate Topic - I Wayan Redhana (Jurnal Cakrawala Pendidikan, 2017)
Abstract: The aim of this research was to investigate the effect of a method of green chemistry practicum on students’ learning outcomes. The study used a quasi-experimental research with non-equivalent pre-test post-test control group design. The population of the study is all students of mathematics and natural sciences of senior high schools in Bali Province. For the aim of the study, it took two parallel classes from one of the senior high schools in Bali Province. In the study, each class consisted of 40 students. One class as a control group was taught by a method of conventional chemistry practicum and another as an experimental group was taught by a method of green chemistry practicum. The results showed that the method of the green chemistry practicum is more effective than that of the conventional practicum in improving students’ learning outcomes. Keywords: green chemistry practicum, conventional chemistry practicum, learning outcomes, reaction rate METODE PRAKTIKUM KIMIA HIJAU UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA TOPIK LAJU REAKSI Abstrak: Penelitian ini bertujuan menyelidiki pengaruh medote praktikum kimia hijau terhadap hasil belajar siswa. Penelitian ini menggunakan penelitian eksperimen semu dengan non-equivalent pre-test post-test control group design. Populasi penelitian ini adalah seluruh siswa MIA SMA di Provinsi Bali. Untuk keperluan penelitian ini, diperlukan dua kelas paralel dari salah satu SMA yang ada di provinsi Bali. Pada penelitian ini, masing-masing kelas terdiri atas 40 orang siswa. Salah satu kelas sebagai kelompok kontrol yang diajar dengan metode praktikum kimia konvensional dan satu kelas yang lain sebagai kelompok eksperimen yang diajar dengan metode praktikum kimia hijau. Hasil penelitian menunjukkan bahwa metode praktikum kimia hijau lebih efektif daripada metode praktikum konvensional dalam meningkatkan hasil belajar siswa. Kata Kunci: praktikum kimia hijau, praktikum kimia konvensional, hasil belajar, laju reaksi